Early targeting of endoneurial macrophages alleviates the neuropathy and affects abnormal Schwann cell differentiation in a mouse model of Charcot‐Marie‐Tooth 1A. Issue 6 (21st February 2022) - Klein, Dennis; Groh, Janos; Yuan, Xidi; Berve, Kristina; Stassart, Ruth; Fledrich, Robert; Martini, Rudolf
Abstract: We have previously shown that targeting endoneurial macrophages with the orally applied CSF‐1 receptor specific kinase (c‐FMS) inhibitor PLX5622 from the age of 3 months onwards led to a substantial alleviation of the neuropathy in mouse models of Charcot‐Marie‐Tooth (CMT) 1X and 1B disease, which are genetically‐mediated nerve disorders not treatable in humans. The same approach failed in a model of CMT1A (PMP22‐overexpressing mice, line C61), representing the most frequent form of CMT. This was unexpected since previous studies identified macrophages contributing to disease severity in the same CMT1A model. Here we re‐approached the possibility of alleviating the neuropathy in a model of CMT1A by targeting macrophages at earlier time points. As a proof‐of‐principle experiment, we genetically inactivated colony‐stimulating factor‐1 (CSF‐1) in CMT1A mice, which resulted in lower endoneurial macrophage numbers and alleviated the neuropathy. Based on these observations, we pharmacologically ablated macrophages in newborn CMT1A mice by feeding their lactating mothers with chow containing PLX5622, followed by treatment of the respective progenies after weaning until the age of 6 months. We found that peripheral neuropathy was substantially alleviated after early postnatal treatment, leading to preserved motor function in CMT1A mice. Moreover, macrophage depletion affected the altered Schwann cell differentiation phenotype. These findings underscore the targetable role of macrophage‐mediated inflammation in peripheral nerves of inherited neuropathies, but also emphasize the need for an early treatment start confined to a narrow therapeutic time window in CMT1A models and potentially in respective patients. Main Points: Genetic inactivation of CSF‐1 alleviates the demyelinating phenotype. Pharmacological macrophage targeting affects Schwann cell differentiation and mitigates neuropathy when applied within an early postnatal time window.